2019
DOI: 10.1002/jctb.6053
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme immobilized on the surface geometry pattern of groove‐typed microchannel reactor enhances continuous flow catalysis

Abstract: BACKGROUND: Enzymatic catalysis in a microchannel under continuous flow has attracted increasing scientific interest. It allows for surfaces with higher specificities for heat and mass transfer and makes it easier to control reaction parameters. However, its applications are limited by a lesser amount of loading and cycle of use of the immobilized enzyme. A series of groove-typed channel microreactors with surface geometry patterns were first established for effective immobilization of naringinase, which was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Results showed that the microreactor enhanced up to 10 times the system productivity compared to the free enzyme form and 30 times compared to the batch immobilized system. The superior characteristics of microreactors in terms of productivity, reaction time, and amount of biocatalysts used in comparison with other types of microreactors are in accordance with the observations made by previous studies by Tušek et al and Zhu et al for surface immobilized enzymes in different microreactor systems. , …”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results showed that the microreactor enhanced up to 10 times the system productivity compared to the free enzyme form and 30 times compared to the batch immobilized system. The superior characteristics of microreactors in terms of productivity, reaction time, and amount of biocatalysts used in comparison with other types of microreactors are in accordance with the observations made by previous studies by Tušek et al and Zhu et al for surface immobilized enzymes in different microreactor systems. , …”
Section: Results and Discussionsupporting
confidence: 90%
“…The superior characteristics of microreactors in terms of productivity, reaction time, and amount of biocatalysts used in comparison with other types of microreactors are in accordance with the observations made by previous studies by Tusěk et al and Zhu et al for surface immobilized enzymes in different microreactor systems. 35,36 Morphological and Optical Characterization of the Developed Microbioreactor. As a proof of concept, the nanostructure developed in the inner walls of the glass capillaries was characterized with electron microscopy and spectroscopic techniques to investigate the morphology of ZnO nanostructures and confirm the effective PEI functionalization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…printed reactors [32] and groove-typed channel microreactors have been tailored to increase the loading capacity [33]. In wall-coated reactors the STY scales reciprocally with the diameter of the channel.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of surface geometry of the microreactor on the immobilization of biocatalysts was also an important parameter. Zhu et al studied the impact of different geometry patterns of groove-typed channel microreactors on the immobilization of naringinase and further investigated the catalytic performance through hydrolysis of rutin-producing isoquercitrin [249]. The groove-type microreactors increased the enzyme adsorbing capacities compared to the smooth surface, giving the maximum of 1.32-fold increment in a triangular pattern.…”
Section: Immobilization Of Biocatalysts On Channel Wallmentioning
confidence: 99%